On some unexpected properties of radial and symmetric eigenvalues and eigenfunctions of the p-Laplacian on a disk - Bobkov, Vladimir; Drábek, Pavel (Journal of Differential Equations, 2017)
We discuss several properties of eigenvalues and eigenfunctions of the p-Laplacian on a ball subject to zero Dirichlet boundary conditions. Among main results, in two dimensions, we show the existence of nonradial eigenfunctions which correspond to the radial eigenvalues. Also we prove the existence of eigenfunctions whose shape of the nodal set cannot occur in the linear case p=2. Moreover, the limit behavior of some eigenvalues as p→1+ and p→+∞ is studied.